2021
DOI: 10.24136/eq.2021.002
|View full text |Cite
|
Sign up to set email alerts
|

Readability, efficiency and costliness of individual retirement products in Poland

Abstract: Research background: The role of supplementary pension systems in providing adequate income in old-age is increasing significantly. They are frequently analysed, but rather in terms of architecture, product forms, assets under management or tax incentives than in terms of their efficiency, costliness or readability for individuals. Purpose of the article: The first aim of this paper is to evaluate individual retirement products in Poland regarding their linguistic readability and transparency, investment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The results support findings of Pieńkowska-Kamieniecka et al, (2021) who also examined the characteristics of individual retirement contracts in Poland but used other linguistic measures and a shorter period for efficiency assessment. But they are contrary to outcomes of the studies by Carlin (2009), Turner (2013) and Cash and Tsai (2018) who found that less readable documents are used in more costly financial services.…”
Section: Variable Fog Indexsupporting
confidence: 82%
See 2 more Smart Citations
“…The results support findings of Pieńkowska-Kamieniecka et al, (2021) who also examined the characteristics of individual retirement contracts in Poland but used other linguistic measures and a shorter period for efficiency assessment. But they are contrary to outcomes of the studies by Carlin (2009), Turner (2013) and Cash and Tsai (2018) who found that less readable documents are used in more costly financial services.…”
Section: Variable Fog Indexsupporting
confidence: 82%
“…pension vehicles are assessed relatively rarely, and only limited studies are devoted to their profitability and readability (Rutecka-Góra et al, 2020;Pieńkowska-Kamieniecka et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent studies on readability, clarity and efficiency of individual pension products in Poland [28,35,36] proved that the difficulty level of individual pension contracts is high and the documents are unclear irrespective of the type of financial provider. However, these studies did not examine the linguistic complexity directly and used only the automatic tools of comprehensibility assessment.…”
Section: Literature Reviewmentioning
confidence: 99%